International migration and development *. Issue 1 (23rd December 2014) - Khatiwada, Sameer; Samaniego, Brenda
Abstract : This chapter seeks to contribute to a better understanding of the incentives behind migration and its effects on economic growth and development for both sending and receiving countries. It provides an overview of the current state of migration across the globe, including stocks and flows of migrants and their basic characteristics. Using data covering 68 countries between 1986 and 2007, the results show that migration has a small positive impact on growth in the receiving countries. Furthermore, an econometric exercise based on a database of 165 countries between 1994 and 2010 reveals that remittances have a positive and significant impact on both savings and investments in the migrant sending countries. The chapter concludes with policy considerations for better leveraging migration and remittances for economic growth, development and poverty reduction.